Digitalization in accounting: impacts of Robotic Process Automation in accounting with a particular outlook on the Accountant's role - Watai, Cintia Lika (2021)
Purpose: New digital technologies in organizations became mandatory. Many publications in renowned scientific journals and consulting firms' research highlight the prominence of Robotic Process Automation (RPA) and its impact in the Finance and Accounting area. Apart from many optimistic and pessimistic outlooks on the effects of RPA in Accounting, this research aims to collect from the perspective of various professionals and specialists working with this tool in the Accounting area: the impacts of RPA in Accounting with a particular outlook on the Accountant’s role. Design/Methodology/approach: It is an exploratory study with a qualitative approach for data collection, based on semi-structured interviews, using the socio-technical lens. The outcome is a report looking for patterns, challenges, ideas, hypotheses on the Accounting professionals' role changes by RPA, captured from experts' perspectives working directly with this tool. Value: The results offer valuable information for organizations and executives to review Accountant professionals' profiles and skills. It can also evaluate their career development plans and reevaluate their job descriptions. Additionally, it can provide insights for Accounting universities departments to review their graduation curriculum matching the market needs with suitable skill sets. As the last contribution, this paper would like to contribute by bringing insights to companies on how to proceed and succeed with RPA implementation. Findings: As a conclusion of this thesis, RPA did not change the role of the Accountants; however, it has impacted the Accounting team skills requirements by migrating the Accounting team into a more hybrid profile, and it has evidenced that many Accountants were doing nonAccounting jobs, spending their time on non-value-added tasks instead of using their skills analyzing data and helping businesses to achieve their goals. RPA is also accentuating the need for digital skillsets for Accountant professionals. Besides soft and hard skills, digital skills such as technology fluency became compulsory.